Analyzing the position of women as evil in the cinema of Masoud Kimiaei - rozhan hesam ghazi; mohamaad nejadiran (فصلنامه زن و جامعه, 2023)
Rejecting myths does not mean destroying all dramatic relations between the sexes, it does not mean denying the meanings that are truly revealed to men during female reality, it does not mean eliminating poetry, love, adventure, happiness and dreams, it just means that It is requested that the basis of behaviors, feelings and desires be based on the truth. Maybe new myths will emerge. (1) Therefore, in this research, we are trying to answer the question, what is the position of women as female subjects in the cinema of Masoud Kimiaei? Let's examine the position of anti-feminist myths in history by emphasizing Simone de Beauvoir's approach in Masoud Kimiaei's cinema to the subject of women as a symbol of nothingness and death and desire taken from historical myths with a feminist approach; Therefore, in Kimiai's works from Caesar to the contemporary period, we will briefly examine the position of women as evil in Masoud Kimiai's cinema. For example, in the film Crime (2009), the filmmaker shows that dependence on women, even if it does not lead to their betrayal or infidelity, can ruin men's lives or lead them to seditious and troublesome behaviors.